2022
DOI: 10.1186/s12915-022-01377-1
|View full text |Cite
|
Sign up to set email alerts
|

Deficient DNA base-excision repair in the forebrain leads to a sex-specific anxiety-like phenotype in mice

Abstract: Background Neuropsychiatric disorders, such as schizophrenia (SZ) and autism spectrum disorder (ASD), are common, multi-factorial and multi-symptomatic disorders. Ample evidence implicates oxidative stress, deficient repair of oxidative DNA lesions and DNA damage in the development of these disorders. However, it remains unclear whether insufficient DNA repair and resulting DNA damage are causally connected to their aetiopathology, or if increased levels of DNA damage observed in patient tissue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 92 publications
0
3
0
Order By: Relevance
“…This may suggest that changes in anxiety occur in both sexes but are captured differently based on sex. In support of this, a recent study investigating the effects of deficient DNA repair on multi-symptomatic disorders found that mice with a conditional knockout for XRCC1 (i.e., a BER protein) displayed increased anxiety in males using the light–dark box test, while increased fear learning was observed in females using fear conditioning ( Mueller et al, 2022 ). Thus, altered DNA repair, elicited here by a BRCA1 heterozygous knockout, may work in a similar manner to differentially alter anxiety-related behaviours in both males and females with rmTBI.…”
Section: Discussionmentioning
confidence: 89%
“…This may suggest that changes in anxiety occur in both sexes but are captured differently based on sex. In support of this, a recent study investigating the effects of deficient DNA repair on multi-symptomatic disorders found that mice with a conditional knockout for XRCC1 (i.e., a BER protein) displayed increased anxiety in males using the light–dark box test, while increased fear learning was observed in females using fear conditioning ( Mueller et al, 2022 ). Thus, altered DNA repair, elicited here by a BRCA1 heterozygous knockout, may work in a similar manner to differentially alter anxiety-related behaviours in both males and females with rmTBI.…”
Section: Discussionmentioning
confidence: 89%
“…The idea that DNA repair deficits underlie PANS and acute decompensation in NDD is novel, although studies linking DDR to behavior have been described. For example, postmitotic genome instability in neurons can lead to behavioral alterations and neurodegenerative disorders, and genetic studies show that DNA repair genes are involved in genetic subgroups of ASD and NDDs including most of the genes described in this report (e.g., PPM1D, ATM, ATR, 53BP1, FANCE, FANCI, and FANCP/SLX4) [113][114][115][116][117][118][119][120] .…”
Section: Discussionmentioning
confidence: 99%
“…DDR also engages the cGAS/STING pathway and stimulates a non-cell-autonomous response that facilitates homeostasis maintenance. However, deregulated DDR causes uncontrolled inflammation and tissue damage, including in the CNS [ 254 , 255 ]. Impaired DNA damage repair in concert with mitochondrial dysfunction is a common feature of diverse psychiatric disorders [ 255 , 256 ].…”
Section: Hallmark 8: Repair and Regenerationmentioning
confidence: 99%